Fish fauna from the Langueyú basin, Argentina: a prairie stream in a heavily modified landscape - Bertora, Andrea (2018)
On the Pampa plain, one of the most productive modified areas of Argentina, important changes in land uses have drastically altered the landscape during the last decades. This has led to an increased deterioration of surface waters affecting fish that inhabit them. We provide a list of fish species inhabiting an unsurveyed prairie stream of this region. Environmental variables were measured and fish samplings were conducted in 3 sites of the Langueyú stream. A total of 15 species belonging to 10 families and 6 orders were collected. Characiformes and Siluriformes were the richest orders. Characidae was the most representative family. Species richness was highest when compared with other similar regional environments without connection with the Salado river basin. Most of the fish species collected are typical of the region but others are species which typically do not progress beyond the Salado river basin. The role of human intervention in fish species distribution is discussed.